The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fmed.2018.00354
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Endothelial Progenitor Cells Toward Their Use in Clinical Translation

Abstract: Since the discovery of Endothelial Progenitor Cells (EPC) by Asahara and colleagues in 1997, an increasing number of preclinical studies have shown that EPC based therapy is feasible, safe, and efficacious in multiple disease states. Subsequently, this has led to several, mainly early phase, clinical trials demonstrating the feasibility and safety profile of EPC therapy, with the suggestion of efficacy in several conditions including ischemic heart disease, pulmonary arterial hypertension and decompensated liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 92 publications
0
71
0
1
Order By: Relevance
“…Yet, they are far from being probed in clinical trials on ischemic patients. A recent article surveyed the clinical studies that probed EPCs as a therapeutic agent against an array of pathologies [ 111 ]. Only 26 out of 341 clinical trials identified by searching the term “EPC” assessed the regenerative outcome of EPCs in severe ischemic disorders, such as CAD, PAD, and stroke, whereas the remaining investigations were of a more observational nature (i.e., they evaluated EPC levels as biomarkers for different pathological conditions).…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, they are far from being probed in clinical trials on ischemic patients. A recent article surveyed the clinical studies that probed EPCs as a therapeutic agent against an array of pathologies [ 111 ]. Only 26 out of 341 clinical trials identified by searching the term “EPC” assessed the regenerative outcome of EPCs in severe ischemic disorders, such as CAD, PAD, and stroke, whereas the remaining investigations were of a more observational nature (i.e., they evaluated EPC levels as biomarkers for different pathological conditions).…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…Only 26 out of 341 clinical trials identified by searching the term “EPC” assessed the regenerative outcome of EPCs in severe ischemic disorders, such as CAD, PAD, and stroke, whereas the remaining investigations were of a more observational nature (i.e., they evaluated EPC levels as biomarkers for different pathological conditions). Five additional trials, which were identified through a search on PubMed and Web of Science databases, were conducted to examine the impact of EPCs-based therapy in PAD, CAD, pulmonary hypertension, and liver cirrhosis [ 111 ]. These studies demonstrated that EPC therapy was feasible and safe; however, it was concluded that the EPC populations employed, deriving either from bone marrow or UCB, were largely heterogenous and mainly consisted of hematopoietic angiogenic cells, such as MACs [ 33 , 111 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, they are far from being probed in clinical trials on ischemic patients. A recent article surveyed the clinical studies that probed EPCs as therapeutic agent against an array of pathologies [121]. Only 26 out of 341 clinical trials identified by searching the term "EPC" assessed the regenerative outcome of EPCs in severe ischemic disorders, such as CAD, PAD and stroke, whereas the remaining investigations were of more observational nature (i.e.…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Improvementioning
confidence: 99%
“…Thus, EPCs are determined as a component of endogenous vascular repair system that supports vascular integrity, endothelial function, angiogenesis, neovascularization and reparation [5]. There is a large of body evidence that decreased number and / or weak function of EPCs known as EPC dysfunction frequently proceeded to developing cardiovascular (CV) disease and / or CV events and also accompanied CV risk factors [6][7][8]. Indeed, declined number of circulating EPCs was associated with CV complications, but restoring of a pole of angiopoetic endothelial precursors was related to an attenuation of vascular function, decreasing of a risk of CV events and improving of clinical outcomes [9,10].…”
mentioning
confidence: 99%